Post-buckling Partial Similitude Scaled Model for Stiffened Cylinders under Axial Compression by Energy Method - Wei Yu; Siyu Du; Wanxu Zhu; Chuntao Zhang (Buildings, 2022)
Considering the geometric nonlinearity and geometric imperfection of stiffened cylinders, the generalized similitude conditions and scaling laws for axial compression post-buckling are established by applying the similitude transformation to the total energy of the structure. The post-buckling similarity of stiffened cylinders is numerically analyzed, and scale laws, through innovative application of the stiffness formulas and deformation scale factor. Based on three type geometrical imperfections, the effects of radius to effective thickness ratios, stiffened cross-sections, boundary conditions and imperfection coefficients are investigated by post-buckling partial similarity simulation of stiffened cylinders under axial compression. The results show that the partial similarity can be well realized by changing other parameters or selecting a model with a similar Poisson’s ratio for the prototypical material on the premise of invariant stiffness scale factors. Partial similarity simulation of axial compression post-buckling of stiffened cylinders is not affected by radius to effective thickness ratios (23.76–268.95), classical simply supported and fixed support boundary conditions, rectangular or T-type stiffened cross-sections and three type of geometric imperfections.